Suppression of Urokinase-Type Plasminogen Activator Receptor by Docosahexaenoic Acid Mediated by Heme Oxygenase-1 in 12-O-Tetradecanoylphorbol-13-Acetate-Induced Human Endothelial Cells - Sen Lian; Shinan Li; Dhiraj Kumar Sah; Nam Ho Kim; Vinoth‐Kumar Lakshmanan; Vinoth‐Kumar Lakshmanan; Young Do Jung (Frontiers Media S.A., 2020)
Urokinase-type plasminogen activator receptor (uPAR) plays a crucial role in inflammation and tumor metastasis. Docosahexaenoic acid (DHA), a representative omega-3 polyunsaturated fatty acid, has been shown to exhibit anti-inflammatory and anti-tumor properties. However, the mechanism by which DHA negatively regulates uPAR expression is not yet understood. The aim of this study was to investigate the effect of DHA on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced uPAR expression and potential role of heme oxygenase-1 (HO-1) in DHA-induced inhibition of uPAR in human endothelial ECV304 cells. Results showed that TPA induced uPAR expression in a time dependent manner, while DHA inhibited uPAR expression in a concentration-dependent manner. Moreover, treatment with DHA induced HO-1 expression in a time- and concentration-dependent manner. In addition, DHA-induced inhibition of uPAR expression and cell invasion in TPA-stimulated cells was reversed by si-HO-1 RNA. Induction of HO-1 by ferric protoporphyrin IX (FePP) inhibited TPA-induced uPAR expression, and this effect was abolished by treatment with the HO-1 inhibitor tin protoporphyrin IX (SnPP). Additionally, carbon monoxide, an HO-1 product, attenuated TPA-induced uPAR expression and cell invasion. Collectively, these data suggest a novel role of DHA-induced HO-1 in reducing uPAR expression and cell invasion in human endothelial ECV304 cells.